A new species of Phanerotoma Wesmael (Hymenoptera: Braconidae: Cheloninae), a parasitoid of Conopomorpha sinensis Bradley (Lepidoptera: Gracillariidae) from South China - Tsang, Winson; You, Lan-Shao; van Achterberg, Cornelis; Liang, Guang-Wen (Zootaxa, 2011)
Phanerotoma conopomorphae sp. nov. (Cheloninae (Hymenoptera: Braconidae) is described and illustrated; a solitary parasitoid of the litchi fruit borer Conopomorpha sinensis Bradley (Lepidoptera: Gracillariidae) of Litchi chinensis Sonn. in Guangdong (South China). The new species is compared with related species from the Oriental region.